1995
DOI: 10.1177/00220345950740060601
|View full text |Cite
|
Sign up to set email alerts
|

Anticariogenicity of Calcium Phosphate Complexes of Tryptic Casein Phosphopeptides in the Rat

Abstract: Casein phosphopeptides (CPP) stabilize calcium phosphate through the formation of casein-phosphopeptide amorphous calcium-phosphate complexes (CPP-CP). The ability of CPP-CP to reduce caries activity was investigated by use of specific-pathogen-free rats inoculated with Streptococcus sobrinus. The animals consumed a defined cariogenic diet free of dairy products. Solutions (100 microL) of the CPP-CP (0.1, 0.2, 0.5, 1.0% w/v) were applied to the animals' molar teeth twice daily. Other groups of animals received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
174
2
14

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 35 publications
7
174
2
14
Order By: Relevance
“…tooth mousse contains casein phosphopeptide (CPP) and amorphous calcium phosphate (ACP). CPP stabilizes ACP and forms nano complexes with ACP at the tooth surface, thereby providing a reservoir of calcium and phosphate ions which favors mineralization [25]. In our study, G.C.…”
Section: Resultsmentioning
confidence: 60%
“…tooth mousse contains casein phosphopeptide (CPP) and amorphous calcium phosphate (ACP). CPP stabilizes ACP and forms nano complexes with ACP at the tooth surface, thereby providing a reservoir of calcium and phosphate ions which favors mineralization [25]. In our study, G.C.…”
Section: Resultsmentioning
confidence: 60%
“…Another view is that casein from cheese, or phosphopeptides from cheese, form complexes which stabilise colloidal calcium phosphate and favour their diffusion into plaque. 17,18 However, ICT experiments have shown that a solution containing calcium and phosphate ions at the same concentrations as found in a 25% w/v aqueous extract of cheese, effectively reduces sucrose-induced demineralisationsuggesting a casein-independent action of these ions. 3 RESEARCH dental caries A wide inter-subject variation in plaque calcium concentration and its increase after cheese consumption has been reported 1, 2,14 and is confirmed in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…The new phosphopeptide isolated from the milk protein casein, complexed with calcium phosphate [Casein phosphopeptide -Amorphous calcium phosphate (CPP -ACP) nanocomplexes], has recently been shown to be efficacious in both the prevention and reversal of enamel subsurface lesions in caries models 3,4,5,6 . The CPP binds to form nanoclusters of calcium and phosphate ions in solutions to form highly soluble and bioavailable nanocomplexes.…”
Section: Discussionmentioning
confidence: 99%